An assessment of the effects of social capital on the income generation of selected FARMCOOP members the case of TCBC, MARBMCO, and PAPCOBAGROW - Javerle, Janice V.
Income generation of farmers is influenced by various factors. One major factor is the inputs such as land, pesticides, and labor. As suggested by some authors, social capital should be considered as an input of production. The study examined if social capital affected the income generation of FARMCOOP members who are engaged in banana farming. The elements like trust, optimism, associatedness, and linkage were considered to test the presenceof social capital. The social capital elements were integrated with income like area planted, operational costs, labor, volume of production, educational attainment and experience in banana farming. The empirical analysis was done using Tobit Model, a non-linear regression. The results of the study showed that MARBMCO members' income is positively affected by linkage while trust did not indicate any effect on income. On the other hand, the income of TCB farmers was not significantly affected by social capital. Collective farming was not observed, instead they did the individual farming system. Such model lessened the responsiveness of the cooperative members to the social capital elements . Nonetheless, in the case of PAPCOBAGROW, composed of indigenous people indicated that their income generation was affected by social capital. This cooperative was formed through the extension program of FARMCOOP in order to serve the community where they operate. This study, therefore, recommends the formation of cooperative which will serve as a viable structure to enable the cooperatives function as a social and business enterprise. Also, regular monitoring of the performance of every member cooperative must be done to address any problem that may arise.